Race and a decolonial turn in development studies. Issue 9 (1st September 2020) - Patel, Kamna
Abstract: This paper reviews and revives a longstanding conversation about race and development studies, which was prominently explored in a collection of papers on race and racism in the journal Progress in Development Studies back in 2006. This revival is timely in the context of a global call to decolonise higher education. Given the central logic of race and racism in European colonialism, and the decolonial argument that colonialism continues in the production and value of knowledge, I examine the presence and absence of race and racism in discussions of decolonising higher education and in development studies. Through a systematic review and content analysis of papers published in six major development studies journals over the past 13 years, I identify where and how race is present in current development scholarship and explore the implications of this for a decolonial turn in development studies.